1981
DOI: 10.1577/1548-8659(1981)110<158:mohrsb>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Movements of Hudson River Striped Bass

Abstract: The movements of age‐II and older striped bass (Morone saxatilis), tagged during 1976 and 1977 within a 70‐km section of the lower Hudson River, were determined from recaptures of fish within and outside the river. Movements within the river prior to and during the spawning period are related to maturity, age, and sex. During March and April, mature and immature fish coexist downriver from the principal spawning grounds. By late April, immature fish tend to migrate downriver and mature fish upriver. Males prec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0

Year Published

1983
1983
2008
2008

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(30 citation statements)
references
References 10 publications
3
27
0
Order By: Relevance
“…Despite high levels of fishing, few striped bass were harvested (approximately 13% of total catch), mainly because of angler concerns about PCB contamination. Although the season is open from March to November, most striped bass fishing occurs from early April to late June (Peterson 1998;NYSDEC 2005), coinciding with the ingress of coastal striped bass in the spring (Clark 1968;McLaren et al 1981;Waldman et al 1990). We have shown that resident striped bass spend over half of the year in freshwater tidal waters, in contrast to migratory striped bass, which spend 1-2 months in this region during their 102 WINGATE AND SECOR spawning run (Clark 1968;Waldman 2006).…”
Section: Discussionmentioning
confidence: 86%
See 2 more Smart Citations
“…Despite high levels of fishing, few striped bass were harvested (approximately 13% of total catch), mainly because of angler concerns about PCB contamination. Although the season is open from March to November, most striped bass fishing occurs from early April to late June (Peterson 1998;NYSDEC 2005), coinciding with the ingress of coastal striped bass in the spring (Clark 1968;McLaren et al 1981;Waldman et al 1990). We have shown that resident striped bass spend over half of the year in freshwater tidal waters, in contrast to migratory striped bass, which spend 1-2 months in this region during their 102 WINGATE AND SECOR spawning run (Clark 1968;Waldman 2006).…”
Section: Discussionmentioning
confidence: 86%
“…Due to logistical constraints of sampling points south of BMB, we only documented an emigration south of our lowest intercept site, and our understanding of winter habitat use by the resident contingent is therefore incomplete. It is likely that resident striped bass overwinter in Haverstraw Bay based upon past tagging studies and the historical fishery that occurred there (McLaren et al 1981(McLaren et al , 1988. Further studies of winter habitat use in the areas of Haverstraw Bay are needed to confirm this expectation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Also, biases in sampling intensity occurred over spatial and temporal scales, compromising interpretations. More recent population-level explanations of Hudson River striped bass migratory patterns specify size-and sex-specific rates of coastal emigration applied to the entire population (McLaren et al 1981, Waldman et al 1990, Dorazio et al 1994, Secor & Piccoli 1996.…”
Section: Introductionmentioning
confidence: 99%
“…Eastern silvery minnow is a freshwater species and it was observed only at the upstream portion of the gradient where water is fresh. Striped bass is an anadromous species that spawns in tidal rivers and migrates to estuarine and marine coastal waters to feed and grow (McLaren et al 1981). This species was observed throughout the Hudson River estuary gradient, but with varied abundance.…”
Section: Abundance Exchange Model Developmentmentioning
confidence: 99%